AB0383 Relationship of RA disease activity classifications and medication usage with ethnicity. (23rd January 2014) - Kerr, G.; Yazici, Y.; Sherrer, Y.; Nair, R.; Treadwell, E.; Mosley-Williams, A.; Espinoza, L.; Garcia-Valladares, I.; Ince, A.; Huang, J.; Nunziato, C.; McCracken, W.A.; et al.
Abstract : Background: Advances in treatment for RA and focus on "treating to target" has led to increased use of disease activity measures in routine care. Little data exists regarding disease activity in ethnic minorities. The Ethnic Minority Rheumatoid Arthritis Consortium (EMRAC) is a registry comprise of RA clinical measures obtained during routine care. Objectives: To evaluate RA disease activity levels and use of DMARDs and biologic agents in ethnic minorities. Methods: RA patients of self-reported ethnicity from 9 US sites are enrolled. Demographics, comorbidities, treatments, disease activity composite scores (RAPID3, CDAI, and DAS289) were collected. Analyses of differences in clinical variables in racial groups was performed using Kruskal-Wallis for continuous variables and exact tests for qualitative variables; post-hoc pairwise comparisons between racial groups were made with the Wilcoxon rank sum test and adjusted using the Bonferonni correction (p<0.008 for significance). Results: 502 RA patients were enrolled (Table). For the RAPID3, DAS28, and CDAI there were not any significant racial differences between categories. Differences between races existed in medications, classified as neither DMARD or biologic, DMARD only, biologic only, and both DMARD and biologic medications. African-Americans had a smaller percentage of patients than Caucasians or Hispanics for biologic use and were more likely to be on DMARDs only rather than combination treatments. Conclusions: Although differences exist in RA treatments amongst ethnic groups, current RA composite disease activity scores appear to be similar. Further analysis is needed to evaluate these findings. Disclosure of Interest: G. Kerr Grant/Research support from: Genentech and Biogen IDEC, Inc, Y. Yazici Grant/Research support from: Abbott, BMS, Centocor, Genentech, Consultant for: Abbott, BMS, Genentech, Celgene, UCB, Y. Sherrer Grant/Research support from: AstraZeneca, Mercke, UCB, Sanofi Adventis, Celgene, Lily, Roche, Amgen, Wyeth, Pfizer, Novartis, Speakers Bureau: AstraZeneca, Human Genome Science, Amgen, Pfizer, Wyeth, R. Nair: None Declared, E. Treadwell: None Declared, A. Mosley-Williams: None Declared, L. Espinoza: None Declared, I. Garcia-Valladares: None Declared, A. Ince: None Declared, J. Huang: None Declared, C. Nunziato: None Declared, W. McCracken: None Declared, C. Swearingen: None Declared